Updates on hosts and distribution of pepper yellow leaf curl Indonesia virus and squash leaf curl China virus in Central Java Province, Indonesia - Adyatma Irawan Santosa; Adenisa Hanifah Irbati; Geby Nandita Cahyaning Pratiwi; Antama Surwadinata; Putri Laeshita; Krisnanda Surya Dharma; Reko Saputra Jaya; Annisa Lisa Andriyani; Chilya Qurrota A'yun; Chusnu Naura Syifa Fatika (Jurnal Ilmiah Pertanian)
Chili pepper, tomato, and squash  cultivated in Magelang Regency, Central Java Province, Indonesia showed severe viral symptoms. Three samples were taken then molecularly tested against begomovirus, potyvirus, tobamovirus, and polerovirus. However, PCR test confirmed only begomovirus infections. BLAST analysis concluded that the chili pepper and tomato isolates were pepper yellow leaf curl Indonesia virus (PepYLCIV) while the squash isolate was squash leaf curl China virus (SLCCNV). The 552 bp partial AV1 gene sequences of the three isolates were given NCBI GenBank acc nos. OR924278-80. PepYLCIV OR924279 and OR924280 formed a subgroup with LC542629 from Bali in the phylogenetic tree constructed using MEGA11, and shared 95.8 – 96.7% identities at nucleotide (nt) and 98.4 – 99.5% at amino acid (aa) levels according to Sequence Demarcation Tool v1.2 software. Meanwhile, SLCCNV OR924278 was clustered, and shared 95.8 – 96.7% nt and 98.4 – 99.5% aa identities with three Malaysian isolates (MW248685, MW248687, and MW248689). Different plant species inoculated with SLCCNV OR924278 remained symptomless up to four weeks observation, suggesting that the isolate is not mechanically transmissible. This study contributed additional knowledge on molecular variation while expanding hosts and distribution of PepYLCIV and SLCCNV in Central Java Province.